Molecular and morphological diagnostic markers for the Himalayan Ips DeGeer species (Coleoptera: Curculionidae: Scolytinae) - Buhroo, Abdul A.; Lakatos, Ferenc (Zootaxa, 2011)
Morphological and molecular analyses of Ips bark beetles collected in the eastern and northwestern Himalayan area resulted in the diagnosis of three species—Ips stebbingi, I. longifolia and I. schmutzenhoferi. These three species can be distinguished by morphological characters, including the frontal setae, the body size and the shape and position of the spines on the elytral declivity. DNA sequences of the mitochondrial Cytochrome Oxidase I gene were analyzed to detect haplotype variation within each of the species. A phylogenetic analysis was performed on our data plus data from GenBank. Considerable amount of intra-specific sequence divergence was found in I. longifolia, ranging between 0.2%−2.5%. Intra-specific sequence divergence in I. stebbingi ranged from 0.2%−1.1% and in I. schmutzenhoferi it varied by 0.2%. Interspecific sequence divergence was high among the three species: 7.4−8.6% between I. longifolia and I. stebbingi, 11.9−12.2% between I. stebbingi and I. schmutzenhoferi, and 11.5−12.6% between I. longifolia and I. schmutzenhoferi. Phylogenetic analyses revealed Himalayan Ips species to be monophyletic and unrelated to other Asian species. Ips stebbingi and I. longifolia were sister taxa and I. schmutzenhoferi was distinguished from I. stebbingi.